Effects of heat acclimation on hand cooling efficacy following exercise in the heat. Issue 9 (3rd May 2017) - Adams, Elizabeth L.; Vandermark, Lesley W.; Pryor, J. Luke; Pryor, Riana R.; VanScoy, Rachel M.; Denegar, Craig R.; Huggins, Robert A.; Casa, Douglas J.
ABSTRACT: This study examined the separate and combined effects of heat acclimation and hand cooling on post-exercise cooling rates following bouts of exercise in the heat. Seventeen non-heat acclimated (NHA) males (mean ± SE; age, 23 ± 1 y; mass, 75.30 ± 2.27 kg; maximal oxygen consumption [VO2 max], 54.1 ± 1.3 ml·kg −1 ·min −1 ) completed 2 heat stress tests (HST) when NHA, then 10 days of heat acclimation, then 2 HST once heat acclimated (HA) in an environmental chamber (40°C; 40%RH). HSTs were 2 60-min bouts of treadmill exercise (45% VO2 max; 2% grade) each followed by 10 min of hand cooling (C) or no cooling (NC). Heat acclimation sessions were 90–240 min of treadmill or stationary bike exercise (60–80% VO2 max). Repeated measures ANOVA with Fishers LSD post hoc (α < 0.05) identified differences. When NHA, C (0.020 ± 0.003°C·min −1 ) had a greater cooling rate than NC (0.013 ± 0.003°C·min −1 ) (mean difference [95%CI]; 0.007°C [0.001, 0.013], P  = 0.035). Once HA, C (0.021 ± 0.002°C·min −1 ) was similar to NC (0.025 ± 0.002°C·min −1 ) (0.004°C [−0.003, 0.011], P  = 0.216). Hand cooling when HA (0.021 ± 0.002°C·min −1 ) was similar to when NHA (0.020 ± 0.003°C·min −1 ) ( P  = 0.77). In conclusion, when NHA, C provided greater cooling rates than NC. Once HA, C and NC provided similar cooling rates.